Synthesis and characterization of light-absorbing cyclopentadithiophene-based donor-acceptor copolymers - Sharma, Bhavna Indrajit; Sarothia, Yameeni; Singh, Ranbir; Kan, Zhipeng; Keivanidis, Panagiotis E.; Jacob, Josemon (My University, 2016)
Cyclopentadithiophene and benzothiadiazole based donor-acceptor polymers are fast emerging as the most promising class of materials for organic solar cells. Here we report on a series of Cyclopentadithiophene and benzothiadiazole based conjugated polymers, namely poly[4,7-bis(4,4-dioctyl-4H-cyclopenta[2,1-b;3,4-b′]dithiophene-2-yl)benzo[1,2,5]thiadiazole] (P1), poly[4,7-bis(4,4-dioctyl-4H-cyclopenta[2,1-b;3,4-b′]dithiophene-2-yl)benzo[1,2,5]thiadiazole-alt-9-(heptadecan-9-yl)-2,7-bis(4,4,5,5-tetramethyl)-1,3,2-dioxaborolan-2-yl)-9H-carbazole] (P2) and poly[4,7-bis(4,4-dioctyl-4H-cyclopenta[2,1-b;3,4-b′]dithiophene-2-yl)benzo[1,2,5]thiadiazole-alt-5,11-bis(2-hexyldecyl)-3,9-bis(4,4,5,5-tetramethyl)-1,3,2-dioxaborolan-2-yl)-5,11-dihydroindolo[3,2-b]carbazole] (P3), with alternating donor and acceptor units and discuss their photophysical and electrochemical properties. Stille coupling of 2-tributylstannyl-4,4-dioctylcyclopenta[2,1-b:3,4-b′]dithiophene with 4,7-dibromobenzo[1,2,5]thiadiazole generated the alternating donor-acceptor monomer 4,7-bis(4,4-dioctyl-4H-cyclopenta[2,1-b;3,4-b′]dithiophene-2-yl)benzo[1,2,5]thiadiazole (CPDT-BT-CPDT). Homopolymer P1 of CPDT-BT-CPDT was synthesized by oxidative polymerization using FeCl3. Copolymers P2 and P3 were synthesized by palladium-catalysed Suzuki polycondensation. The synthesized polymers showed good solubility in common organic solvents, and UV-visible measurements showed that the absorption maxima of the polymers lie in the range 624 to 670 nm. The energy gaps of these polymers were found to lie in the range 1.29 to 1.50 eV. Gel permeation chromatography measurements against polystyrene standards showed the number-average molecular weight to be in the range (2.2-6.0) × 104 g mol-1. Thermogravimetric analysis showed the polymers to possess high thermal stability. A preliminary study of photodiode devices prepared using polymers P1, P2 and P3 when blended with the PC71BM electron acceptor found that P2 is the optimum chemical structure for pursuing further device optimization.
Keywords: Benzothiadiazole; Cyclopentadithiophene; Organic solar cells; PCBM